1996
DOI: 10.1111/j.1365-2125.1996.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine as a metabolic probe: NAT2 phenotyping

Abstract: Caffeine has been used to determine acetylator phenotype for some 15 years but the interpretation of metabolic ratios with this substance raises theoretical and methodological issues. N-acetyltransferase type 2 (NAT2) status was assessed in 23 young healthy subjects using both caffeine overnight and spot urine samples, and sulphadimidine. Frequency distribution analysis of the metabolic ratios of NAT2, indicated two distinct groups for sulphadimidine, and for caffeine spot but not overnight samples. Spearman's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Twenty‐four healthy nonsmoking volunteers were enrolled who were not taking any over‐the‐counter or prescribed medications when they presented to the research clinic (a minimum of 12 hours free of such medications was required). Within 12 weeks before administration of study medication, participants completed a caffeine phenotype probe screening study to determine eligibility and acetylator status by analysis of urinary caffeine metabolites 28 , 29 . During the open‐label, single‐visit screening study, participants received a single oral dose of 200 mg caffeine (Vivarin) with 240 mL water following an overnight fast, having agreed to refrain from over‐the‐counter and prescription medications, as well as xanthine‐containing food and beverage ingestion, for at least 12 hours.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐four healthy nonsmoking volunteers were enrolled who were not taking any over‐the‐counter or prescribed medications when they presented to the research clinic (a minimum of 12 hours free of such medications was required). Within 12 weeks before administration of study medication, participants completed a caffeine phenotype probe screening study to determine eligibility and acetylator status by analysis of urinary caffeine metabolites 28 , 29 . During the open‐label, single‐visit screening study, participants received a single oral dose of 200 mg caffeine (Vivarin) with 240 mL water following an overnight fast, having agreed to refrain from over‐the‐counter and prescription medications, as well as xanthine‐containing food and beverage ingestion, for at least 12 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Values (ng/mL) were converted to nM, and the molar 5‐acetyl‐amino‐6‐formyl amino‐3‐methyluracil/1‐methylxanthine ratio for each participant was calculated. A slow acetylator phenotype was defined by a ratio of ≤0.55 and a fast acetylator phenotype by one of >0.55 28 , 29 . The mean (range) of ratios of the 12 participants identified as fast acetylators (7 men and 5 women) enrolled into this study was 1.18 (0.749–1.669) and that of the 12 participants identified as slow acetylators (7 men and 5 women) was 0.184 (0.00–0.39).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two primers NAT2F 5′-TGGGCTTAGAGGCTATTT and NAT2R 5′-GAGTTGGGTGATACATACAC were designed using Primer Express version 2.0 software (Applied Biosystems Inc, Foster City, CA, USA) to amplify a 768 bp sequence of the second exon of the NAT2 gene which contains the relevant polymorphisms (G191A, C282T, T341C, C481T, G590A, A803G, G857A). Following purification (QIAgen PCR purification kits, QIAGEN, United Kingdom) amplicons were sequenced (3130xl Genetic Analyzer Applied Biosystem, Hitachi, Singapore) and phenotypes predicted from genotypes previously defined in a cohort of healthy Vietnamese volunteers in a study correlating urinary caffeine metabolites ratios with NAT2 genotypes (data not shown) [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Express version 2.0 software (Applied Biosystems Inc, Foster City, CA, USA), to amplify a 768 bp sequence of the relevant polymorphisms on the NAT2 gene (G191A, C282T, T341C, C481T, G590A, A803G, G857A). The phenotype were predicted from the genotype, using a previously defined correlation between genotype and urinary caffeine metabolite ratio in a cohort of healthy Vietnamese volunteers (54,57,58).…”
Section: Downloaded Frommentioning
confidence: 99%